What outcome measures are most useful in measuring the effectiveness of anti-dementia medication in people with intellectual disabilities and dementia?. Issue 2 (2nd May 2022) - Ghazirad, Marjan; Hewitt, Olivia; Walden, Sarah
Abstract : Purpose: The use of anti-dementia medication in people with intellectual disabilities has been controversial and requires additional research to assess the efficacy of such medications. An essential part of this treatment (both in terms of research and clinical practice) is having robust outcome measures to assess the efficacy of these medications for individuals. Currently there is no consensus in the UK regarding which outcome measures, in conjunction with clinical judgement, are effective in informing clinicians' decision-making regarding anti-dementia medication management and this paper aims to present useful outcome measures. Design/methodology/approach: A comprehensive literature search was conducted to identify relevant outcome measures. Outcome measures focused on aspects of patients' presentation such as cognition, activities of daily living, neuropsychiatric presentation or the impact of their presentation (either on themselves, or on others). These outcome measures were critically appraised to ascertain their suitability in informing clinician's decisions regarding management of anti-dementia medication. The focus of this appraisal was on good quality measures that are practical and accessible and can be easily used within clinical NHS services. Findings: This paper provides advice for clinicians on using appropriate outcome measures, depending on patients' presentations and the symptoms of dementia being targeted, that can be used alongside their clinical assessment to enhance their anti-dementia medication management. Two case studies are presented to illustrate the use of such outcome measures. Originality/value: The case for using a range of assessments that are both broad in focus, and those specifically selected to measure the areas of functioning targeted by the anti-dementia medication, is presented.